Ellipsis In The Narrative Structure Of Ghassan Kanafani’s Men In The Sun - Mohammed, Rana Waleed; Hazem, Ali Hussein; Salman, Zahraa Muharam (Ijaz Arabi Journal of Arabic Learning, 2025)
Ellipsis in language is not just the dropping of words or phrases but rather a means of condensation and suggestion, as it allows the reader to reconstruct the meaning and explore what lies behind the words. Ghassan Kanafani invested this method in his novel to express the loss and disorientation experienced by his characters and to create an open space for contemplation of the suffering and pain of the Palestinian people. The novel Men in the Sun by the Palestinian writer Ghassan Kanafani is one of the most prominent literary works that deals with the issue of displacement and the Palestinian struggle in a unique artistic style. In exploring this distinctive text's creative and semantic aspects, ellipsis emerged as one of the linguistic methods the writer relied on to express meanings indirectly, adding deep aesthetic and suggestive dimensions to the text. The current study aims to shed light on the manifestations of and analyze its linguistic and semantic functions in the text and how it enhanced the humanitarian and political messages the writer wanted to convey. Moreover, the impact of ellipsis on the reader's experience and the extent of its success as an artistic tool in enriching the novel's narrative structure is reviewed.